Innovation community and content providers' new service development performance in technology-based service ecosystem. Issue 10 (1st September 2020) - Li, Lei; Liu, Bo; Mu, Huimin
Abstract : Purpose: This paper investigates the paths through which innovation community affects content providers' new service development (NSD) performance in technology-based service ecosystem and contingency factors exist in the paths. Design/methodology/approach: The research model is built based on service-dominant (S-D) logic, exploring the relationship among innovation community, content providers' knowledge acquisition and content providers' NSD performance as well as the moderating role of content providers' technology readiness and content providers' complexity. Using survey data collected from 386 content providers of selected open network platforms in China, this study finds broad support for the proposed research model. Findings: The findings of this paper reveal that content providers' tacit knowledge acquisition from users plays a mediating role between the innovation community and new service ratings. Content providers' technology readiness plays a positive moderating role in the relationship between innovation community and their explicit or tacit knowledge acquisition. Content providers' task complexity negatively moderates the effects of their explicit knowledge acquisition from users on new service volumes or ratings, but positively moderates the effects of tacit knowledge acquisition from users on new service volumes or ratings. Originality/value: Though extant literature highlights the importance of knowledge acquisition in NSD performance, few studies explore the antecedents of content providers' knowledge acquisition from users and the paths through which these antecedents affect content providers' NSD performance. Moreover, boundary conditions exist in the process of improving NSD performance are generally ignored in previous literature. With the lens of S-D logic, this paper explicates how content providers of different technology readiness and different task complexity enhance their new service volumes and ratings through acquiring explicit and tacit knowledge from users in innovation community. Adopting S-D logic from marketing area to NSD area, this paper not only enriches the theoretical accumulations of antecedents and boundary conditions of content providers' NSD performance but also offers insights for content providers and users on how to synergistically advance NSD activities and co-create value in the technology-based service ecosystem.